Physicians' awareness and practice of home blood pressure measurement in Indonesia: Asia home blood pressure monitoring survey 2020 - Yuda Turana; Noriko Matsushita; Ebtehal Salman; Arieska Ann Soenarta; Vidya Gani Wijaya; Bambang Widyantoro; Eka Harmeiwaty; Rarsari Soerarso; Tunggul Diapari Situmorang (Universa Medicina, 2023)
Background Hypertension is a significant mortality risk factor. The knowledge and practice among physicians of hypertension management and home blood pressure monitoring (HBPM) in blood pressure control is important. We aimed to investigate the awareness and practice of HBPM among physicians in Indonesia after publishing of the local 2019 HBPM guidelines.